2004
DOI: 10.5194/acp-4-275-2004
|View full text |Cite
|
Sign up to set email alerts
|

New insights in the global cycle of acetonitrile: release from theocean and dry deposition in the tropical savanna of Venezuela

Abstract: Abstract. Using the proton transfer reaction mass spectrometry (PTR-MS) technique, acetonitrile was measured during the wet season in a Venezuelan woodland savanna. The site was located downwind of the Caribbean Sea and no biomass burning events were observed in the region. High boundary layer concentrations of 211±36 pmol/mol (median, ±standard deviation) were observed during daytime in the well mixed boundary layer, which is about 60 pmol/mol above background concentrations recently measured over the Mediter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 21 publications
4
20
1
Order By: Relevance
“…Assuming a boundary layer height of 125 m and a median nighttime mixing ratio of 0.11 ppbv, we obtain a dry deposition velocity of 0.16 cm s −1 (Table 3) which is consistent with the 0.14 cm s −1 value reported for a tropical savanna ecosystem (Sanhueza et al, 2004).…”
Section: Biomass Burning Tracer -Acetonitrile (Ch 3 Cn M/z 42)supporting
confidence: 78%
See 1 more Smart Citation
“…Assuming a boundary layer height of 125 m and a median nighttime mixing ratio of 0.11 ppbv, we obtain a dry deposition velocity of 0.16 cm s −1 (Table 3) which is consistent with the 0.14 cm s −1 value reported for a tropical savanna ecosystem (Sanhueza et al, 2004).…”
Section: Biomass Burning Tracer -Acetonitrile (Ch 3 Cn M/z 42)supporting
confidence: 78%
“…None of these loss processes are particularly efficient, leading to a lifetime in the atmosphere of ∼0.5-1.5 y depending upon whether an ocean sink is considered (former) or removal is restricted to wet deposition and reaction with OH (latter) (Hamm et al, 1984;Hamm and Warneck, 1990;Singh et al, 2003). Recent work (Sanhueza et al, 2004) has indicated that the ocean may act as a reservoir for acetonitrile, being a source in warm regions and a sink in cold regions.…”
Section: Biomass Burning Tracer -Acetonitrile (Ch 3 Cn M/z 42)mentioning
confidence: 99%
“…It is possible that a biological sink for acetonitrile, which is not present in the Gulf of Guinea, is required to drive ocean uptake (Bange and Williams, 2000). Along with the measurements of Sanhueza et al (2004) over the Caribbean Sea, from which they inferred net release of acetonitrile from the ocean, the observations presented in this paper indicate that the ocean cannot always be considered a sink for acetonitrile.…”
Section: Profiles Over the Oceanmentioning
confidence: 70%
“…Benzene is predominantly emitted during fossil fuel combustion and biomass burning and it has a lifetime of 10 days against oxidation by OH. It is believed that biomass burning is the main source of acetonitrile to the atmosphere (de Gouw et al, 2003c), while estimates of its atmospheric lifetime range from ∼1 year against oxidation by OH, to months if ocean uptake is assumed to be significant (de Gouw et al, 2003c;Sanhueza et al, 2004;Singh et al, 2003). The global atmospheric budget of acetone, reviewed in Jacob et al (2002), includes primary sources from anthropogenic and biogenic emissions and a photochemical ocean source, in addition to secondary production from oxidation of anthropogenic and biogenic VOC.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in the mixing ratios in these two altitude regions can therefore be attributed to entrainment of air during the convective uplift of the lower tropospheric air. A biomass burning plume as a cause of the upper-level trace gas enhancement can be excluded because acetonitrile, a distinct tracer for biomass burning, is not significantly enhanced (Lobert et al, 1990;Holzinger et al, 1999;Sanhueza et al, 2004). The mixing ratios of O 3 , NO, OH and HO 2 are remarkably high.…”
Section: Measurement Datamentioning
confidence: 98%